Increasing impact of North Atlantic Ocean circulation on sedimentary processes along the passive Galicia Margin (NW Spain) over the past 40 million years - Haberkern, Julia; Hanebuth, Till J. J.; Spiess, Volkhard; Schwenk, Tilmann (Frontiers in Earth Science, 2024)
Off the Northwestern Iberian Peninsula, the vigorous bottom-current regime interacts with a complex seafloor topography inside the Galicia Interior Basin (GIB), which was tectonically shaped during the opening of the North Atlantic Ocean basin in Cretaceous times. The evolving North Atlantic Ocean circulation determined the depositional pattern of the basin fill over time, which can, in turn, be utilized as palaeoceanographic archive. This study reconstructs the evolution of the GIB sedimentary system since the mid-Eocene, namely, resulting from interplay between down- and along-slope sediment-transport processes, using high-resolution multichannel seismic data. Six major depositional stages are identified and connected to the evolution of the North Atlantic Ocean circulation. 1) Levelling of topography shows that the influence of contourparallel bottom currents on the depositional pattern steadily intensified since the mid-Eocene; 2) The strengthening of Northern Component Water (NCW), associated with the opening of the Faeroe-Shetland Basin in the late Eocene, is documented along the southwestern European continental margin for the first time by the onset of a plastered contourite drift; 3) A shift in the depocenters provide evidence that the closure of the Tethys-Indian Seaway led to Tethys Outflow Water into the Atlantic Ocean at intermediate ocean depths in the Miocene; 4) Until the mid-Miocene, the tectonic stress regime initially associated with the Pyrenean Orogeny and the following Betic Orogeny led to both sets of small-scale faulting systems as well as submarine mass wasting indicated by slope scarps and mass-transport deposits; 5) The onset of modern-style Mediterranean Outflow Water (MOW) after the Messinian Salinity Crisis (5.3 Ma) caused a distinct change in the depositional dynamics from combined along- and down-slope transport processes towards predominantly contouritic deposition, which is evident from the construction of several separated mounded contouritic drifts that formed during Pliocene and early Pleistocene times; and 6) The contourite drift growth continued during the middle and late Pleistocene, but under a gaining influence of down-slope processes.